Factors Influencing the Antenatal Care Attendance of Pregnant Women During the First COVID-19 Wave Lockdown in Thailand - Chalermpichai T. (2023)
Background: The coronavirus disease 2019 (COVID-19) outbreak impacted healthcare service management worldwide. Thailand had limited healthcare resources. During the pandemic, several medical supplies were in high demand and expensive. The Thai government needed to declare a lockdown to reduce the unnecessary use of medical supplies. Antenatal care (ANC) services have adapted to the outbreak situation. However, information about the potential impact of COVID-19 lockdown on pregnant women and the reduction of disease exposure risk in this population remains unclear. Thus, this study aimed to assess the percentage of ANC attendance and factors affecting the scheduled ANC attendance of pregnant women during the first COVID-19 wave lockdown in Thailand. Methods: This retrospective cross-sectional study included Thai women who were pregnant between 1 March and 31 May 2020. An online survey was conducted among pregnant women who had first ever ANC attendance before 1 March 2020. A total of 266 completed responses were returned and analysed. Statistically, the sample size was representative of the population. The predictors of scheduled ANC attendance during the lockdown were identified through logistic regression analysis. Results: Overall, 223 (83.8%) pregnant women had scheduled ANC attendance during the lockdown. The predictive factors of ANC attendance were non-relocation (adjusted odds ratio [AOR] = 2.91, 95% confidence interval [CI]: 1.009–8.381) and access to health services (AOR = 2.234, 95% CI: 1.125–4.436). Conclusion: During the lockdown, ANC attendance slightly declined, and the extended duration of each ANC or reduced face-to-face interactions with healthcare professionals. For pregnant women with non-relocation, healthcare providers must provide opportunities to contact them directly if they had doubts. The limited number of pregnant women who access health services allowed the clinic to be less crowded and therefore easy to ANC attendance.